2016
DOI: 10.18632/oncotarget.12751
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus X protein influences enrichment profiles of H3K9me3 on promoter regions in human hepatoma cell lines

Abstract: We previously showed that hepatitis B virus (HBV) X protein (HBx) could promote the trimethylation of histone H3 lysine 9 (H3K9me3) to repress tumor suppressor genes in hepatocellular carcinoma (HCC). In this work, we analyze 23,148 human promoters using ChIP-chip to determine the effects of HBx on H3K9me3 enrichments in hepatoma cells with transfection of HBx-expressing plasmid. Immunohistochemistry for HBx and H3K9me3 was performed in 21 cases of HBV-associated HCC tissues. We identified that H3K9me3 immunor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…1f ). Btbd17 has no known function besides epigenetic dysregulation in hepatocellular carcinoma 29 , while Grasp regulates neuronal intracellular trafficking and metabotropic glutamate receptor organization 30 . In contrast, EPlo uniquely and differentially expressed Fev and St18 , a paralog of Myt1.…”
Section: Resultsmentioning
confidence: 99%
“…1f ). Btbd17 has no known function besides epigenetic dysregulation in hepatocellular carcinoma 29 , while Grasp regulates neuronal intracellular trafficking and metabotropic glutamate receptor organization 30 . In contrast, EPlo uniquely and differentially expressed Fev and St18 , a paralog of Myt1.…”
Section: Resultsmentioning
confidence: 99%
“…HBx protein also promotes the proliferation of hepatoma cells. Wang et al found that HBx downregulated tumor-suppressor p16 gene by methylation of some CpG sites in the promoter region [44]. HBx protein activates the Wnt/β-catenin pathway which results in the acceleration of hepatoma cell proliferation [45].…”
Section: Introductionmentioning
confidence: 99%
“…While ZNFs are best known as DNA-binding domains, it has become clear that ZNF domains can bind with RNA, lipids, and methylated DNA, as well as proteins and PTMs such as SUMO, ubiquitin, PAR, and methylation [36] . A few ZNF proteins have been reported to be associated with viral infection [ 37 , 38 ]. Among the reports already available about ZNF205, no report is relevant to viral infection.…”
Section: Discussionmentioning
confidence: 99%